2022
DOI: 10.1021/acs.nanolett.2c02475
|View full text |Cite
|
Sign up to set email alerts
|

A Nanounit Strategy Disrupts Energy Metabolism and Alleviates Immunosuppression for Cancer Therapy

Abstract: Aberrant energy metabolism not only endows tumor cells with unlimited proliferative capacity but also contributes to the establishment of the glucose-deficient/lactate-rich immunosuppressive tumor microenvironment (ITM) impairing antitumor immunity. Herein, a novel metabolic nanoregulator (D/B/CQ@ZIF-8@CS) was developed by enveloping 2-deoxy-d-glucose (2-DG), BAY-876, and chloroquine (CQ) into zeolitic imidazolate framework-8 (ZIF-8) to simultaneously deprive the energy/nutrition supply of tumor cells and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Further studies have revealed that the tumor growth rate positively correlates with glucose levels and that high glucose levels in cancer patients are associated with poor prognosis [ 7 , 8 , 9 ]. Thus, cancer starvation therapy based on glucose deprivation is emerging as an effective treatment for suppressing tumor growth [ 10 , 11 , 12 ]. For example, the ketogenic diet can inhibit the metabolic proliferation of cancer cells by reducing blood glucose [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have revealed that the tumor growth rate positively correlates with glucose levels and that high glucose levels in cancer patients are associated with poor prognosis [ 7 , 8 , 9 ]. Thus, cancer starvation therapy based on glucose deprivation is emerging as an effective treatment for suppressing tumor growth [ 10 , 11 , 12 ]. For example, the ketogenic diet can inhibit the metabolic proliferation of cancer cells by reducing blood glucose [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hexokinase 2-DG is an effective HK inhibitor to repress the Warburg effect phenotype of cancers (Pouysségur et al, 2022). Luo et al (2022) designed a novel multi-targeted nano drug termed D/B/ CQ@ZIF-8@CS enveloping 2-DG, BAY-876 (GLUT1 inhibitor), and chloroquine (CQ), which sufficiently inhibits the aerobic glycolysis procedure of cancer cells. Significantly, the drug synthetically improves the anti-CTLA-4 immunotherapy efficacy by reducing Tregs metabolic fitness in the relieved TME, which is used to be glucose-deficient and lactateenriched (Luo et al, 2022).…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%
“… Luo et al (2022) designed a novel multi-targeted nano drug termed D/B/CQ@ZIF-8@CS enveloping 2-DG, BAY-876 (GLUT1 inhibitor), and chloroquine (CQ), which sufficiently inhibits the aerobic glycolysis procedure of cancer cells. Significantly, the drug synthetically improves the anti-CTLA-4 immunotherapy efficacy by reducing Tregs metabolic fitness in the relieved TME, which is used to be glucose-deficient and lactate-enriched ( Luo et al, 2022 ). In ovarian cancer, Tregs pretreated with 2-DG also alleviate the inhibition of effector T cell proliferation ( Xu et al, 2021b ).…”
Section: Available Glycolysis-targeted Therapiesmentioning
confidence: 99%
“…[1] In recent years, T-cell-based immunotherapy, such as immune checkpoint inhibitors, therapeutic tumor vaccines, and chimeric antigen receptor (CAR) T-cell therapies, has become a rising strategy for promoting systemic immune detection and eliminating primary tumors, as well as metastatic tumors. [2][3][4][5] Despite T cells based immunotherapy having been shown to be effective in some DOI: 10.1002/smtd.202201327 patients and providing consistent clearance of tumor cells in advanced metastatic tumors, the efficiency is still limited due to the low responsiveness and insufficient infiltration of T cells. [6] Therefore, it is highly reasonable to improve the response and infiltration of T cells by converting "cold tumors" (tumors with weak tumor immunogenicity) into "hot tumors" (tumors with strong immunogenicity).…”
Section: Introductionmentioning
confidence: 99%